IMPLEMENTATION OF LEARNING MODELS TEAM GAME TOURNAMENT TO IMPROVE STUDENTS 'ENGLISH LEARNING ACHIEVEMENT (A class Action Research at Grade X IPA-2 MAN 1 Pati 2019/2020) - Bambang Budiyono (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2020)
The purpose of this study was to determine whether the Team Game Tournament (TGT) Learning Model improves the English learning achievement of students of The class X IPA-2 odd semester Madrasah Aliyah Negeri 1 Pati in the 2019/2020 academic year. The design of this study is a classroom action research conducted in three cycles. Each cycle consists of planning, implementing, observing and reflecting. The research subjects were students of The class X IPA-2 odd semesters Madrasah Aliyah Negeri 1 Pati in the 2019/2020 academic year. The research variables consist of student achievement variables and teacher activity variables. The data collection method is the observation questionnaire method, and the test method. The data analysis method is qualitative data analysis. From the results of the study, information was obtained that there was an increase in the English learning achievement of The class X IPA-2 students in the odd semester of Madrasah Aliyah Negeri 1 Kudus for the 2019/2020 academic year. This increase is indicated by: (1) the average student achievement in cycle I is 7.14; in the second cycle cycle was 7.44; and in cycle III is 8.84; (2) student learning completeness in cycle I was 17 students or 47.22% and 19 students or 52.78% who did not complete; in cycle II students who completed were 26 students or 72.22% and those who did not complete were 10 students or 27.78%; in cycle III, students who completed 36 students or 100% and there were no students who did not complete; (3) completeness of classical learning in the first cycle was 47.22%, in the second cycle it was 72.22; and in cycle III it reaches 100%. This means that it has reached the predetermined indicator. Besides that, there is also an increase in student activity during the learning process, both individually and in groups. Student responses or responses to the application of the TGT learning model were classified as high, reaching 83.14%.